2021
DOI: 10.1021/acs.energyfuels.1c01072
|View full text |Cite
|
Sign up to set email alerts
|

Study of Sheetlike BiOI/Rodlike Bi5O7I Composite Photocatalyst by In Situ Crystallization of BiOI with pH-Dependence for Hg0 Removal

Abstract: The sheetlike BiOI/rodlike Bi5O7I photocatalysts were prepared through an in situ crystallization method of BiOI with different pH values under alkaline condition. All the physicochemical properties of samples were tested by chemical characterization analysis. The results showed that the different preparation conditions of BiOI photocatalysts presented different microstructures under different pH values. When the value of pH increased from 8 to 14, the morphology of the sample gradually changed from sheetlike … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…In addition, XRD revealed that the crystal structure of Lap-BiOI-pH3 shows increased growth along (110), ( 103), ( 200), (202), and (212) planes of BiOI, whereas Lap-BiOI-pH11 appears to be a mix of BiOI and Bi 5 O 7 I (Figure S8). 43,44 These findings were supported by MD simulations, which showed that layered silicate nanosheets at high pH had little association with PVP at either the edge or basal surface of the clay (Figure 4c−g).…”
Section: ■ Results and Discussionmentioning
confidence: 54%
“…In addition, XRD revealed that the crystal structure of Lap-BiOI-pH3 shows increased growth along (110), ( 103), ( 200), (202), and (212) planes of BiOI, whereas Lap-BiOI-pH11 appears to be a mix of BiOI and Bi 5 O 7 I (Figure S8). 43,44 These findings were supported by MD simulations, which showed that layered silicate nanosheets at high pH had little association with PVP at either the edge or basal surface of the clay (Figure 4c−g).…”
Section: ■ Results and Discussionmentioning
confidence: 54%
“…Currently, several heterojunctions have been reported between PDIs and bismuth-based semiconductors, including PDIs/BiVO 4 , 41 PDIs/Bi 2 W 2 O 6 , 42,43 PDIs/Bi 2 O 4 , 44 PDIs/BiOBr/Bi 4 O 5 Br 2 , 45 and PDIs/BiOX (X = Cl, Br, I). 28,45,46 For example, Ji et al 47 developed a novel type II heterojunction of aky-like BiOCl/PDIs by adjusting the selfassembly time of PDIs. Comparing the photocatalytic activity of the rst self-assembled PDIs with BiOCl (BiO-Cl/PDIs-1) to the second self-assembly with PDI BiOCl (BiOCl/PDIs-2), it was found that the latter showed a better performance for the degradation of cationic dyes.…”
Section: Pdi/inorganic Semiconductor Heterojunctionsmentioning
confidence: 99%
“…As early as the 1930s, it was found that TiO 2 could bleach dyes and degrade fibers in the presence of oxygen and under ultraviolet irradiation, and it was confirmed that TiO 2 remained stable before and after the reaction . Since its discovery in the 1970s, photocatalysis technology has become an perfect technology to alleviate the energy crisis, help with environmental pollution control, and form new countermeasures for superbugs and epidemic viruses . Since the discovery of the catalytic characteristics of semiconductors, people have begun to explore the factors affecting the reaction process of semiconductor photocatalysis.…”
Section: Primary Photocatalytic Theory and Associated Mechanismsmentioning
confidence: 99%